Feasibility study for inhalable heavy metals and respirable silica dust exposures at a municipal landfill - Minchak, Thomas, author; Brazile, William, advisor; Arnold, Olivia, committee member; Gutilla, Molly, committee member (Colorado State University. Libraries, 2025)
Occupational respiratory exposures are a significant exposure route in the United States, with millions of workers in required respiratory protection programs, due to workplace exposures to fumes, dusts, bioaerosols, particles, and other respiratory hazards. Exposure to excessive workplace respiratory hazards may lead to occupational diseases such as silicosis, heavy metals poisoning, or impacts to various organs including the lungs, liver, and kidneys. One work sector that has not been evaluated for respiratory workplace exposures are landfill workers. There are 22,302 municipal landfill workers in the United States across. Landfill worker exposures are of concern since this population operates heavy machinery like construction operations, potentially exposing the workers to airborne hazards. This study was conducted to quantify airborne exposures to landfill workers and to identify the risks that are associated with their daily tasks. The researchers aimed to (1) determine airborne heavy metal particles to which landfill workers are exposed; (2) determine the exposure to respirable silica particles; and (3) identify current worker protections and their effectiveness based on the study results. Nine silica and nine heavy metal personal airborne samples were taken on seven landfill workers during their normal workday tasks. Worker exposure concentrations were compared to occupational exposure limits published by the US Occupational Safety and Health Administration (OSHA) and the American Conference of Governmental Industrial Hygienists (ACGIH) when there was no OSHA exposure limit. Of the seven workers sampled, one worker had a single sample in exceedance of the OSHA Action Limit for silica at 31.1 ug/m3 while the overall 95th percentile of all samples was at 28.89 ug/m3. Many of the heavy metal samples were non-detectable which limited the statistical analysis. All iron sample results were less than 1% of the OSHA Permissible Exposure Limit (PEL) of 10 mg/m3 and manganese samples were at 12% of the ACGIH Threshold Limit Value of 0.01 mg/m3. Sample analytical detections did occur for aluminum, magnesium, and zinc, but the metals had less than 50% detection rate. These samples were statistically analyzed but none showed any substantial levels of exposure, all within the American Industrial Hygiene Association's Category 0, meaning that the concentrations were less than 1% of their respective occupational exposure limits. Mitigations in exposure with a focus on silica have been considered for the landfill site, including emphasis on the effectiveness of proposed and existing engineering controls and assuring that these controls are able to operate at their designed efficiency. Workers exposed above the action limit for silica have an increased risk of respiratory disease. As noted in a National Institute for Occupational Safety and Health (NIOSH) action limit publication, "The action limit is set to minimize the probability of even a low percentage of daily employee exposure exceed the standard" which confirms that exceedances at or above the action limit should initiate careful attention to monitor for the potential of day-to-day overexposures to workers. Worker exposure to heavy metals should be investigated further, since this was a feasibility study with a small sample size, but collected data has variability in whether there was an elevated risk to respiratory health.
Keywords: industrial hygiene; heavy metals; silica